La mandrágora de Amato Lusitano: edición, traducción y anotación - González Manjarrés, Miguel Ángel; Lopes Andrade, Antonio Manuel; Miguel Mora, Carlos de; Nunes Torrão, João Manuel (Aveiro: Universidade de Aveiro, 2015)
Se presenta una edición latina y traducción castellana anotada del capítulo de la mandrágora que incluyó Amato Lusitano (1511-1568) en sus "Enarrationes" (Venecia 1553) a Dioscórides. Se trata de plantear un posible modelo de trabajo para la edición y traducción de la obra completa, tal como se presentó en su día dentro del proyecto de Investigación “Dioscórides e o humanismo português: os Comentários de Amato Lusitano”.
The chapter about mandrake in Amatus Lusitanus’s "Enarrationes" (Venice 1553) is here edited in Latin and translated to Spanish. The text is also annotated. The article is a case-study for editing and translating the Amatus’s whole comments on Dioscorides, and it was already presented at a workshop of the research project “Dioscorides and the Portuguese humanism: the Amatus Lusitanus’s Comments”.
Keywords: Amato Lusitano, -- 1511-1568; Edición; Traducción